Electrochemical Sensor Based on Carboxymethyl Cellulose-Coated Copper Nanoparticle Composite for Detection of Norfloxacin in Milk - LI Shengnan, HU Minkang, QIN Boyang, YANG Wen, FENG Jun, DU Haijun (Shipin Kexue)
A highly sensitive electrochemical sensor for the detection of norfloxacin (NFX) was constructed using CMC@Cu/CB composites, which were prepared from carboxymethyl cellulose (CMC)-coated copper nanoparticles (Cu NPs) and carbon black (CB). The structure and morphology of CMC@Cu/CB were characterized by scanning electron microscope (SEM), X-ray photoelectron spectroscopy (SPS), and X-ray diffraction (XRD). The CMC@Cu/CB/GCE sensor was prepared by drop-casting the composite suspension on the glassy carbon electrode (GCE) surface. The results showed that the CMC@Cu/CB/GCE sensor, which was in the form of uniformly dispersed spheres, had a good current response to NFX, with a linear range of 0.4–100.0 μmol/L and a limit of detection (LOD) of 0.24 μmol/L (RSN = 3). In addition, the modified electrode had good sensitivity and stability for the detection of NFX in real samples, and the spiked recoveries of NFX in milk extracts ranged from 98.8%–112.5%. Furthermore, thanks to the low price of raw materials used in the experimental process and the preparation extremely of low cost of the sensor, it is promising for actual applications.